Examining object location and object recognition memory in mice - Vogel-Ciernia, Annie; Wood, Marcelo A (Current protocols in neuroscience, 2014)
This unit is designed to provide sufficient instruction for the setup and execution of tests for object location and object recognition in adult mice. This task is ideally suited for the study of a variety of mouse models that examine disease mechanisms and novel therapeutic targets. By altering several key parameters, the experimenter can investigate short-term or long-term memory and look for either memory impairments or enhancements. Object location and object recognition memory tasks rely on a rodent's innate preference for novelty, and can be conducted sequentially in the same cohort of animals. These two tasks avoid the inherent stress induced with other common measures of rodent memory such as fear conditioning and the Morris water maze. This protocol covers detailed instructions on conducting both tasks, as well as key points concerning data collection, analysis, and interpretation.